counterpoint Selected models from Nahj al-Balaghah of Imam Ali, peace be upon him (Journal of the College of Basic Education, 2023)
Nahj al-Balaghah represents a tributary of the tributaries with which Arabic literature has been fed, since the era of Imam Ali, peace be upon him, to our time, and this is not surprising, as this speech was emanated from an eloquent tongue, masterful of the aspects of eloquence, owner of the curse of speech, wonderful speeches were made on his tongue, and many The useful commandments, which have been reformed and reformed over time, and therefore many scholars have been concerned with the explanation of (Nahj al-Balaghah), but the most famous of them is the explanation of Ibn Abi al-Hadid al-Madaini (d. 655 AH). Which we adopted in this field of our research, and we decided to confine it to a specific characteristic that would be a field for rhetorical reading, with selected models as well, because the field of research in this great book is wide and does not stop at certain limits.The study focused on two rhetorical terms that are overlapping in the words of Imam Ali, peace be upon him, and they are counterpoint and resonance. Through the research, we tried to look at how they overlap in the text through the criterion of searching for the unfamiliar in the text first, then how counterpoint harmonizes with resonance semantically, to create a linguistic structure. Rhythmic contrapuntal or (opposite) as some call it.